Potions for Emotions: Do self-reported individual differences in negative-emotional drinking predict alcohol consumption in the laboratory following exposure to a negative experience?. (June 2020) - Austin, Henry R.T.; Notebaert, Lies; Wiers, Reinout W.; Salemink, Elske; MacLeod, Colin
Highlights: Increased alcohol consumption in response to negative emotion can be observed in the laboratory. This phenomenon is best predicted by self-reports on observable behavior and not by drinking motives. Abstract: Aims: Research suggests that self-reports on inferred motives for engaging in behavior may be biased by limited introspective access into such processes. Self-reports on observable behavior, on the other hand, may generate more accurate responses with which to predict behavior. The aim was to determine whether drinking alcohol in response to negative emotion ( negative-emotional drinking; NED ) is best predicted by self-reported individual differences in ( a ) motives to use alcohol to regulate negative emotion, or ( b ) the degree to which negative emotion impacts alcohol consumption (observable behavior). Methods: Thirty-nine beer drinkers completed the Drinking Motives Questionnaire-Revised (DMQ-R) which measures individual differences in drinking motives, including the motive to regulate negative emotion (coping motives). They also completed a new self-report measure of the degree to which negative emotion impacts their alcohol consumption. Participants were randomized into a negative emotion induction condition or control condition and completed a subsequent alcohol consumption task to serve as a behavioral measure of drinking in response to negative emotion. Results: Self-reports on the degree to which negative emotion impacts respondents' alcohol consumption strongly predicted alcohol consumption in the negative emotion induction condition ( r = 0.72, p = <.001) and not in the control condition ( r = 0.09, p = .696). Self-reported coping motives did not predict alcohol consumption in either condition. Conclusions: The amount of alcohol consumed in response to negative emotion is best predicted by self-reports on observable behavior, and not by self-reports on drinking motives.